Specimen Pooling as a Diagnostic Strategy for Microbiologic Confirmation in Children with Intrathoracic Tuberculosis. Issue 6 (June 2019) - Walters, Elisabetta; van der Zalm, Marieke M.; Demers, Anne-Marie; Whitelaw, Andrew; Palmer, Megan; Bosch, Corné; Draper, Heather R.; Schaaf, H. Simon; Goussard, Pierre; Lombard, Carl J.; Gie, Robert P.; Hesseling, Anneke C.
Abstract : Three-hundred four young children with suspected pulmonary tuberculosis had a gastric aspirate, induced sputum and nasopharyngeal aspirate collected on each of 2 consecutive weekdays. Specimens collected on the second day were pooled in the laboratory for each child individually. The diagnostic yield by Xpert and culture from pooled specimens was not significantly different to a single gastric aspirate. Abstract : Supplemental Digital Content is available in the text.